Membangun Loyalitas Pelanggan Melalui Peran Citra Sebagai Variabel Intervening - Azlan Azhari (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study aims to analyze the strategy in building customer loyalty through Customer Relationship Marketing, product quality, and price with image as an intervening variable at Daeng Nakku Coffee Shop. The issues raised are whether CRM, product quality, price have a direct and indirect effect on image and loyalty? The population in this study were the customers or visitors of the Daeng Nakku coffee shop. The sample used was 95 samples with accidental sampling technique. Data collection method using survey method with research instrument is a questionnaire. The approach method used in this study is a quantitative method with data analysis tools using Smart PLS. The results showed that the CRM variables, product quality, and price directly had a positive and significant effect on the image of the shop. Furthermore, the CRM variables, product quality, and price directly have a positive and significant effect on customer loyalty. And the image variable can mediate the relationship between CRM, product quality, and price on customer loyalty.Keywords: Image, CRM, Price, ProductQuality, Loyality